Respon Pertumbuhan Dan Hasil Tanaman Sawi Putih (Brassica Pekinensis L.) Akibat Pemberian Dosis Kasgot Kotoran Ayam Dan Konsentrasi PGPR Akar Bambu - Rismayanti Meilani, Fenny; Abdullah, Rohana; Masnenah, Endeh; Samsul Mustopa, Asep (OrchidAgro, 2024)
Chicory (Brassica pekinensis L.), a leaf vegetable that can grow in subtropical and tropical climates, has high economic value, but its production is still relatively small. The provision of BSF and PGPR frass is expected to increase soil organic matter content and nutrient availability for chicory plants. This experiment was carried out at the Experimental Garden, Cikidang Village, Lembang District, West BandunggRegency, at an altitudeeof 1,250 meterssabove sea level, in the Andisol soil order. This study aims to study the interaction between different doses of cassava and the best concentrations of bamboo root PGPR on the growth and yield of mustard plants. The study used a factorial Randomized Block Design (RBD) with two factors, namely BSF frass doses, namely 0 g, 25 g, 50 g, and 75 g, and PGPR concentrations of bamboo roots, concentrations of 0 ml/L water, 10 ml/L water, 20 ml/L water, and 30 ml/L water; each treatment was repeated four times. The results showed no interaction between BSF frass doses and bamboo root PGPR concentrations on the growth and yield of chicory plants. The presence of bamboo roots' PGPR and BSF frass causes the chicory plants' high response at 30 HST. The best dose of chicken manure is 75 grams per plant, and the PGPR concentration of bamboo roots is 10 ml per liter of water. Keywords: Chicken Manure Kasgot, Bamboo Root PGPR, Chinensis cabbage